Efficacy and safety of ombitasvir/paritaprevir/ritonavir and dasabuvir with low‐dose ribavirin in patients with chronic hepatitis C virus genotype 1a infection without cirrhosis. Issue 8 (6th May 2019) - Poordad, Fred; Sedghi, Shahriar; Pockros, Paul J.; Ravendhran, Natarajan; Reindollar, Robert; Lucey, Michael R.; Epstein, Michael; Bank, Leslie; Bernstein, David; Trinh, Roger; Krishnan, Preethi; Polepally, Akshanth R.; et al.
Abstract: Patients infected with hepatitis C virus (HCV) treated with interferon‐free direct‐acting antivirals may still require ribavirin. However, ribavirin is associated with adverse events that can limit its use. This open‐label, multicentre, Phase 3 study evaluated the safety and efficacy of ombitasvir/paritaprevir/ritonavir + dasabuvir (OBV/PTV/r + DSV) with low‐dose ribavirin for 12 weeks in genotype 1a‐infected patients without cirrhosis. The primary efficacy endpoint was sustained virologic response at post‐treatment Week 12 (SVR12). The primary safety endpoint was haemoglobin <10 g/dL during treatment and decreased from baseline. Overall, 105 patients enrolled. The SVR12 rate was 89.5% (n/N = 94/105; 95% CI, 83.7‐95.4). The study did not achieve noninferiority versus the historic SVR12 rate for OBV/PTV/r + DSV plus weight‐based ribavirin. Five patients experienced virologic failure, four discontinued, and two had missing SVR12 data. Excluding nonvirologic failures, the SVR12 rate was 94.9% (n/N = 94/99). One patient met the primary safety endpoint. OBV/PTV/r + DSV plus low‐dose ribavirin offers an alternative option for patients in whom full‐dose ribavirin may compromise tolerability, although noninferiority to the weight‐based ribavirin regimen was not met.